Modulation of Cytokine and Cytokine Receptor/Antagonist by Treatment with Doxycycline and Tetracycline in Patients with Dengue Fever - J. E. Z. Castro; I. Vado-Solis; C. Perez-Osorio; T. M. Fredeking (Clinical and Developmental Immunology)
Dengue virus infection can lead to dengue fever (DF) or dengue hemorrhagic fever (DHF). Disease severity has been linked to an increase in various cytokine levels. In this study, we evaluated the effectiveness of doxycycline and tetracycline to modulate serum levels of IL-6, IL-1B, and TNF and cytokine receptor/receptor antagonist TNF-R1 and IL-1RA in patients with DF or DHF. Hospitalized patients were randomized to receive standard supportive care or supportive care combined with doxycycline or tetracycline therapy. Serum cytokine and cytokine receptor/antagonist levels were determined at the onset of therapy and after 3 and 7 days. Cytokine and cytokine receptor/antagonist levels were substantially elevated at day 0. IL-6, IL-1β, and TNF remained at or above day 0 levels throughout the study period in untreated patients. Treatment with tetracycline or doxycycline resulted in a significant decline in cytokine levels. Similarly, IL-1RA and TNF-R1 serum concentrations were elevated at baseline and showed a moderate increase among untreated patients. Both drugs resulted in a significant rise in IL-1Ra levels by day 3 in patients. In contrast, treatment did not affect a similar result for TNF-R1. When compared to the control group, however, a significant rise post-treatment was seen upon intragroup analysis. Further analysis demonstrated that doxycycline was significantly more effective at modulating cytokine and cytokine receptor/antagonist levels than tetracycline.